Zero‐anaphora resolution in Korean based on deep language representation model: BERT. Issue 2 (25th October 2020) - Kim, Youngtae; Ra, Dongyul; Lim, Soojong
Abstract: It is necessary to achieve high performance in the task of zero anaphora resolution (ZAR) for completely understanding the texts in Korean, Japanese, Chinese, and various other languages. Deep‐learning‐based models are being employed for building ZAR systems, owing to the success of deep learning in the recent years. However, the objective of building a high‐quality ZAR system is far from being achieved even using these models. To enhance the current ZAR techniques, we fine‐tuned a pre‐trained bidirectional encoder representations from transformers (BERT). Notably, BERT is a general language representation model that enables systems to utilize deep bidirectional contextual information in a natural language text. It extensively exploits the attention mechanism based upon the sequence‐transduction model Transformer. In our model, classification is simultaneously performed for all the words in the input word sequence to decide whether each word can be an antecedent. We seek end‐to‐end learning by disallowing any use of hand‐crafted or dependency‐parsing features. Experimental results show that compared with other models, our approach can significantly improve the performance of ZAR.